Analisis kemampuan berpikir tingkat tinggi siswa SMP dalam menyelesaikan soal matematika tipe HOTS - Fallentza, Delya Sekar Ayu; Setyawati, Rina Dwi; Rahmawati, Noviana Dini (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This research is motivated by the last grades of higher order thinking skill students about resolving HOTS-type mathematics test. The problem on how the higher order thinking skills that student have when conducted analysis by based on SOLO taxonomy (The Structure of The Observed Learning Outcome). The purpose of this study is to describe the higher order thinking skill students of Class VIII SMP N 5 Pati in solving HOTS-type math problem. The type of this research is qualitative approach in finding the quality of students ' responses/answers in solving HOTS-type math problems based on SOLO taxonomy. The data collection was carried out by using the document analysis and interviewing data analysis about linear equation system of two variables. Data collection have done entirely online (via whatsApp app). The written test was followed by 8 students of Grade VIII A SMP Negeri 5 Pati. A written test divided into 3 sessions. Data analysis techniques used the data analysis model of Miles and Huberman. The validity test is carried out with data reduction, data display, and conclusion drawing/verification. The triangulation used the triangulation method by comparing the results of the interviews with the written test results that have been done before. Of 8 students who take the test can be divided into 3 level of ability consists multistructural, relational and extended abstract. The most apparent factors are: (1) lack of students in doing practices with similar types of problems; (2) students who less thorough during the test or solving problem.